The optimization of wind turbine placement using a binary artificial bee colony algorithm with multi-dimensional updates - Hakli, Huseyin (Electric power systems research, 2023)
•An artificial bee colony algorithm is binarized by a simple and efficient way.•This binary variant was implemented to wind turbine placement problem.•The proposed method was analyzed with multi-dimensional updates on the problem.•Various methods and binary ABC variants were compared with the proposed method.•The results show that proposed method is a successful tool for binary optimization. Optimal placement of wind turbines on wind farms by considering cost and total power is an important optimization problem. This study uses an artificial bee colony (ABC) algorithm to solve the wind turbine placement problem. The ABC, performing on continuous search space, is adapted to address problems with a binary structure through a proposed simple and effective approach. Because a single-dimensional update for binary form could weaken the ABC algorithm's population diversity and exploration ability, a multi-dimensional update is performed in the proposed method. Multi-dimensional updates are first applied to employed bee and onlooker bee phases of the ABC algorithm separately and together for different dimensions and then analyzed on a 2 km×2 km wind farm area divided into a 10×10 grid. The wind turbine placement problem is also applied for a 20×20 grid structure that makes more flexible placement by dividing the wind area into more sections. The proposed method has a better or comparable level of performance in both grid structures and is an effective method for wind turbine placement. Moreover, the proposed method is compared with different binary ABC variants to show and validate its performance, and it performs better than these variants by solution quality and robustness.